HOW I LIVE NOW BY MEG ROSOFF: WOMEN STRUGGLE IN PATRIARCHY (PANOPTICON: Journal of English Studies, 2022)
This study is entitled â€œHow I Live Nowâ€ by Meg Rosoff, Women's Struggles in Patriarchy.â€ This study discusses women's struggles and how the protagonists overcome them in Meg Rosoff's novel How I Live Now (2004). Daisy is a teenager from the city who falls in love with her cousin on a farm. However, Daisy has to split up and fight to meet her cousin because of the third world war. After a long struggle, Daisy was finally able to visit her cousin at her home in London. Therefore, this study uses the descriptive method. Qualitative methods are used to describe, analyze, and interpret narrative elements to build an understanding of women's struggles and how women manage them. In further research, the data were analyzed using the theory of Simone de Beauvoir (1949) and Judith Butler (1993) as the basic concepts and framework. This study reveals some of the problems of women's struggles in dealing with issues that gradually change in line with the events in the novel. The problem that raises the patriarchal issue experienced by women in their social life, such as at work and during activities in society, leads to the disclosure of the efforts made by the main character to be able to change the patriarchal treatment received.Keywords: Social system, Womenâ€™s struggle, Simone de Beauvoir, Gradual change, Main power